Fibrolamellar Carcinomas are Positive for CD68 - Ross, Hillary M (2010)
Fibrolamellar carcinomas are a unique type of liver carcinoma that arise in non-cirrhotic livers of young individuals. Despite their distinctive appearance, recent studies have demonstrated a lack of consistency in how fibrolamellar carcinomas are diagnosed by pathologists. As a potential aide in diagnosis, we investigated the staining properties of CD68. The CD68 gene encodes for a transmembrane glycoprotein located within lysosomes and endosomes. Macrophages as well as other cell types rich in lysosomes/endosomes are CD68 positive. Cases of fibrolamellar carcinoma were collected from four academic centers. Control groups included hepatocellular carcinomas arising in both non-cirrhotic livers and cirrhotic livers. A group of cholangiocarcinomas were also stained. CD68 immunostaining was scored for both intensity and distribution on a scale of 0 to 3+. Twenty-three primary fibrolamellar carcinomas and 9 metastases (total of 24 individuals) were immunostained and showed a distinctive granular, dot-like or stippled pattern of cytoplasmic staining in nearly all cases (31/32), with a median distribution and intensity score of 3+. In control hepatocellular carcinomas that arose in non-cirrhotic livers, 10/39 showed CD68 staining with a median distribution and intensity score of 2+. In hepatocellular carcinomas arising in cirrhotic livers, 3/27 cases showed CD68 positivity, all with stippled dot-like cytoplasmic staining similar to that of fibrolamellar carcinomas. All 5 cholangiocarcinomas were negative. Overall, CD68 positivity was strongly associated with fibrolamellar carcinomas, p<0.001 and had a sensitivity of 96%, a specificity of 80% and a negative predictive value of 98%. In sum, tumor positivity for CD68 staining was highly sensitive for fibrolamellar carcinoma and a lack of CD68 staining should suggest caution in making a diagnosis of fibrolamellar carcinoma.